Rudolph Agricola: Six Lives and Erasmus's Testimonies - Akkerman, Fokke (bibliotheca latinitatis novae, 2012)
Rudolph Agricola: Six Lives and Erasmus's Testimonies The Frisian humanist Rudolph Agricola (1443-1485) is rightly famous for single-handedly bringing the Italian Renaissance to the North. Owing to his fascinating personality and many talents, he attracted the love and admiration of his contemporaries and the following generations. As a result, six biographies on Agricola have been preserved. The authors of these lives drew their materials from different sources and wrote their texts independently from each other. Differing vastly in rhetorical aims and methods, they provide us with a vivid image of cultural and intellectual life in the 15th century. Erasmus praised Agricola's work throughout his writings. No less than fifty testimonies from Erasmus and his correspondents are presented here. This edition of sources supplements the volume of Agricola's letters (BLN, 2002) and is preceded by an expert survey of all biographical information now at our disposal. Thus it fills a gap in our knowledge of a great man of letters, while correcting a number of persistent misconceptions (concerning the year of Agricola's birth, for instance).